The attitude of medical students to vaccination against COVID-19 - V. A. Anokhin; G. R. Khasanova; S. V. Khaliullina; S. T. Agliullina (Фундаментальная и клиническая медицина, 2022)
Aim. To determine the attitude of medical students to the vaccination against COVID-19.Material and Methods. We conducted an anonymous survey of 756 students and residents of Kazan State Medical University from December, 1st to December, 31th, 2021, using a specially designed Google questionnaire. The questionnaire included questions aimed at assessing the level of awareness about the prevention of COVID-19 and attitude to vaccination.Results. The median age of the respondents was 22 (19; 24) years. The vast majority of the respondents (94.0%, 711/756) received at least one dose of the vaccine, while 92.6% (700/756) subjects underwent a full vaccination. Vaccination rates were similar in students and residents. Despite rather high reactogenicity of vaccine preparations, none of the respondents experienced a strong reaction requiring a hospital admission. The asymptomatic course of the post-vaccination period after the frst and the second doses of the vaccine was noted by 4.8% and 14.5% respondents, respectively. The majority of respondents (58.9%, 445/756) believed that vaccination signifcantly reduces the risk of COVID-19 and 70% (529/756) supposed that vaccination protects against severe COVID-19 and death. The majority of respondents (53.7%) considered appropriate to introduce a mandatory vaccination against COVID-19, and 71.6% of respondents disagreed with the physicians opposing the vaccination.Conclusion. The study revealed a high level of adherence to vaccination among the medical students and residents.